Low-Noise Chopper-Stabilized Zero-Drift Amplifier With SAR-Assisted Automatic Offset Calibration Loop - Gibae Nam; Gyuri Choi; Mookyoung Yoo; Sanggyun Kang; Byeongkwan Jin; Hyeoktae Son; Kyounghwan Kim; Jihyang Wi; Seungmin Ahn; Hyoungho Ko (IEEE Access)
This paper presents a low-noise chopper-stabilized zero-drift amplifier with successive approximation register (SAR)-assisted automatic offset calibration loop (AOCL). The amplifier is designed using multipath zero-drift architecture including a low frequency path (LFP) and a high frequency path (HFP). The multipath architecture can achieve the low offset, the low noise and the low drift while maintaining the wide bandwidth. The LFP amplifier exploits a chopper scheme to reduce the offset and the low-frequency noise components. The digitally assisted AOCLs in the LFP and the HFP using SAR and current-mode digital-to-analog converter (DAC) can reduce the offset coarsely. The mismatch and the offset of the LFP amplifier can generate the up-modulated output ripples. The residual ripples in the LFP can be reduced using a ripple reduction loop (RRL). To prevent secondary ripple caused by the offset of the RRL itself, an auto-zero (AZ) integrator is employed. The HFP amplifier is designed using the folded-cascode structure with class-AB output stage to enhance the power efficiency. The multipath amplifier is fabricated in a $0.18 ~μ \text{m}$ CMOS process. The current consumption, supply voltage and active area are $130 ~μ \text{A}$ , 1.8 V and 0.86 mm2, respectively. The amplifier has a unit gain bandwidth (UGBW) of 0.875 MHz, an input referred offset of $4.6 ~μ \text{V}$ , an input referred noise of 25.6 nV/ $\surd $ Hz, an offset drift of 53 nV/°C and a noise efficiency factor (NEF) of 11.2.